Control of coherent extreme-ultraviolet emission around atomic potential through laser chirp - Yang, Chun; Lou, Zhiyuan; Yang, Fan; Ge, Xiaochun; Zheng, Yinghui; Zeng, Zhinan; Li, Ruxin (Frontiers in Physics, 2022)
Substantial neutral atoms can tunnel to excited states in an intense laser field and subsequently generate coherent emission through free induction decay. We experimentally observe an enhanced coherent emission in the harmonic slightly below the threshold, which is consistent with the free induction decay of Rydberg states produced by the frustrated tunnelling ionization (FTI) process. We further find that the intensity of the coherent emission significantly depends on the chirp of laser pulses. The simulations based on strong field approximation model show that laser chirp affects the probability that the returned electrons recombine to the Rydberg states. Our result shows that coherent emission can be controlled by laser chirp, which facilitates understanding the dynamics of the Rydberg atom and coupling mechanism between the below-threshold harmonics and atomic energy level. In addition, the coherent below-threshold FTI emission we observed has small divergence which is good for EUV light source applications.